Estudo da tecnologia de vasos separadores utilizados na indústria petroquímica - Luxo, Gabriel Ranieri [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The oil industry has a great importance on the Brazilian and world wide markets. The extracted fluid are used in many different processes, one of them is the energy generation in power plants. Therefore, it is need to be conditioned (specific conditions of temperature, pressure, purity, etc.) One of these processes is the separation of the dispersed phases separation. Meaning removing liquid droplets from a gas or vice versa. In order to do so, separator vessels are used. These vessels can the three phase (separation of water, oil and gas) or two phase (separation of water and oil, water and gas or oil and gas). In this paper a study of the internal components of the vessels identifying the application and purpose of each item. After this step a methodology was developed in order to choose and dimension separating vessels. Two cases were focused, two-phase separator and three phase separator with boot. From this method, an example of two-phase dimensioning was showed and a real three-phase separator was evaluated. It was concluded that the three phase separator attended to the requirements and that the use of a boot was correctly chosen. Although, the control times for controlling the water levels in the boot were too high, not condemning the vessel but a smaller boot could have been chosen

A indústria petrolífera tem uma grande importância no mercado brasileiro e mundial. Os fluidos extraídos são utilizados em diversos processos, entre eles, para geração de energia em termelétricas. Para tanto, precisam ser condicionados (condições específicas de temperatura, pressão, pureza, etc). Um dos processos é a separação das fases diversas num fluido, ou seja, retirar gotículas de líquido dispersas num gás e vice-versa. Para realizar esta separação são utilizados vasos separadores. Estes vasos podem ser trifásicos (separação de água, óleo e gás) ou bifásicos (separação de duas fases como água e óleo, água e gás ou óleo e gás). Neste trabalho foi realizado um estudo dos componentes internos dos vasos, identificando o propósito da aplicação de cada item. Após esta etapa foi feita uma metodologia para seleção e dimensionamento de vasos separadores, focando em dois casos: vaso separador bifásico e vaso separador trifásico com bota. A partir deste método, foi mostrado um exemplo de dimensionamento de um vaso separador bifásico separando água e óleo. Então foi analisado um vaso separador trifásico real. Foi concluído que o vaso trifásico atendeu aos requisitos impostos pela metodologia definida e que o uso de uma bota foi corretamente selecionado. Porém, os tempos de controle para água neste vaso ficaram muito altos, apesar de não acarretarem em prejuízos, poderia ser selecionada uma bota menor
Study of separator vessel technology used in the petrochemical industry
Keywords: Indústria petroquímica; Fluidos; Separadores (Maquinas); Petroleum chemical industry